KEMAMPUAN MENULIS SURAT RESMI SISWA KELAS VIII SMP N I PANTI KABUPATEN PASAMAN TAHUN PELAJARAN 2013/2014 - Yusuf, Marsya risona; Chan, Wirsal; Zulfitriyani, Zulfitriyani (Pendidikan Bahasa Indonesia, 2013)
This study discusses the ability of the Official Letter Grade of SMP NI Pasaman Panti. The background of this problem, namely the First, students are not informed about any course sections and subsections official letter. Second, students watched less effective use of sentences. Third, students pay less attention to the use of capital letters , especially the letter of application for a license. Fourth, students are less able to write a formal letter due to several factors, namely ( 1 ) in accordance with the times, students are more likely to use mobile phone communication tool of the write ( 2 ) write a formal letter is a lesson that is less attractive to students. (3) the lack of attention and guidance in writing a formal letter. The purpose of this study is to describe the ability to write an official letter grade SMP N 1 Panti Pasaman, especially letters permit application in terms of sections and subsections of a formal letter, use effective sentences and use capital letters. This paper suggests several theories that are relevant to the variables studied. The theories used are (1) The nature of the letter, include: (a) Definition of a formal letter, (b) a formal letter type, (c) the form of an official letter, (d) parts of a formal letter, (2) effective use of sentence (3) the use of capital letters. This research is quantitative research using descriptive methods. The research data was obtained by a written test or write a letter carried by the eighth grade students . This test aims to determine the ability of students to write a formal letter letter of application for a permit in particular by applying the theories that have been studied. The results of this study as follows. (1) the ability to write an official letter grade SMP N 1 Panti Pasaman for sections and subsections official letter on qualification